K10[Co4(H2O)2(B-α-SiW9O34H)2]·21H2O : a sandwich polyoxometalate based on the magnetically interesting element cobalt - Zhang, Li-Zhi (2012)
The magnetism of a sandwich tetracobalt(II) substituted tungstosilicate K10[Co4(H2O)2(B-α-SiW9O34H)2] · 21H2O has been studied based on an isotropic Heisenberg model supplemented by a zero-field splitting term.